Manajemen Peserta Didik; Proses Pembelajaran Online Pada Peserta Didik Di Tengah Pandemi Covid-19 Studi Kasus di SMK Terpadu Al-Ishlahiyah Singosari Malang - Maulida Qurratul Aini (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
As an educational institution that is superior in terms of religious education and creativity, SMK Terpadu Al-Islahiyah Singosari – Malang, always got praises and awards from various competitions and performances. This things certainly makes proud of all the components that are in SMK Terpadu Al-Ishlahiyah. But since of corona virus or commonly called covid - 19, the institution of education is predicted is the easiest place for covid - 19 to spread, because of the activities that are always done in groups. This is what makes the interest of the author to investigate this issue further. The existence of covid – 19 pandemic seems to be a test for educational institutions. All educational institutions in Indonesia is required to be able to keep running the learning process in this pandemic situation. The government decided to do online learning because of this situation. as what SMK Terpadu Al-Ishlahiyah has done, they are also implementing online learning in this pandemic situation.This study uses a qualitative method in the form of interviews, in addition, this study also carried out by way of review of the literature to corroborate the explanation of the results of the interview. This is done to determine how the application of management students in the learning process in the middle of the pandemic of covid - 19 in SMK Terpadu Al-Ishlahiyah. As well as the impact or what obstacles are given Covid - 19 to the learning process of learners.